Rhythm is it: effects of dynamic body feedback on affect and attitudes - Koch, Sabine C. (Frontiers in psychology, 2014)
This paper investigates effects of dynamic body feedback on affect, attitudes, and cognition, focusing on the impact of movement rhythms with smooth vs. sharp reversals as one basic category of movement qualities. It investigates how those qualities relate to already explored effects of approach vs. avoidance motor behavior as one basic category of movement shaping. Studies 1 and 2 tested the effects of one of two basic movement qualities (smooth vs. sharp rhythms) on affect and cognition. The third study tested those movement qualities in combination with movement shaping (approach vs. avoidance motor behavior) and the effects of those combinations on attitudes toward initially valence-free stimuli and affect. Results suggest that movement rhythms influence affect (studies 1 and 2), and attitudes (study 3), and moderate the impact of approach and avoidance motor behavior on attitudes (study 3). Extending static body feedback research with a dynamic account, findings indicate that movement rhythms can moderate and go beyond effects of approach and avoidance motor behavior.